Pembuatan Aplikasi DVR Driving dengan Fitur GPS dan Live Streaming Berbasis Android - David Christian Hidajat; Agustinus Noertjahyana; Kristo Radion Purba (Jurnal Infra, 2017)
Currently, vehicles has become important for human life to go from one place to another place. Now there is a tool called Car DVR which is a tool for recording events during the trip in video form, but Car DVR which has a feature to record location data and good video result is relatively expensive.Therefore, in this thesis made an Android application that has functions such as Car DVR but equipped with GPS and live streaming. With this application user can record video complete with location data and map. This application also can be used to share traveling experiences to anyone else through the live video streaming along with the location data in real-time.The test results showed that this application is able to record videos with location data and map nicely. The accuracy of location data and map is affected by the quality of internal GPS Android. Live streaming feature requires a stable internet connection and upload speeds above 1 Mbps to get good result.